PENCAPAIAN INDIKATOR NASIONAL MUTU RUMAH SAKIT DI INDONESIA - Ruri Purwandani; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Background: The National Quality Indicator Measurement (INM) of hospitals is mandatory to be conducted as a basis for planning, monitoring, evaluation, and decision-making for the improvement of healthcare services in hospitals, following Minister of Health Regulation Number 30 of 2022. Objective: This study aims to determine the overview of the achievement of hospitals in Indonesia in reporting and meeting the National Quality Indicators (INM). Method: The method used in this study is descriptive with secondary data analysis. Quality indicator data was obtained from the achievement data of national quality indicators reported in the mutu fasyankes.kemenkes.go.id/simar/ application. Results: All provinces have implemented the reporting of INM measurements, and the number of hospitals reporting INM in the first quarter of 2023 has increased compared to the reporting of hospital INM in the fourth quarter of 2022. There are still 18 provinces with INM reporting compliance below 50%. There is no difference in reporting compliance between government/TNI/POLRI-owned hospitals, state-owned enterprises, and private hospitals. The average achievement of INM targets in 2023 has improved compared to 2022. Compliance with the use of Personal Protective Equipment (PPE) is an indicator of low achievement. Conclusion and Suggestions: Compliance in reporting INM by hospitals has increased after the implementation of the obligation to measure and report INM according to Minister of Health Regulation Number 30 of 2022. However, the achievement of the compliance indicator for the use of PPE is still low. It is necessary to strengthen healthcare workers' adherence to the use of PPE.